Facile synthesis of nanocrystalline-assembled nest-like NiO hollow microspheres with superior lithium storage performance. Issue 50 (19th June 2017) - Li, Yanwei; Zheng, Yuanyuan; Yao, Jinhuan; Xiao, Jianrong; Yang, Jianwen; Xiao, Shunhua
Abstract : Interconnected nest-like NiO hollow microspheres assembled from nanocrystallites are prepared by a facile hydrothermal method followed by annealing at 700 °C in air. Abstract : Interconnected nest-like NiO hollow microspheres assembled from nanocrystallites are prepared by a facile hydrothermal method followed by annealing at 700 °C in air. It is noteworthy that the NiO hollow microspheres exhibit a very significant pseudocapacitive effect which makes a great contribution to the enhanced lithium storage performance. Benefiting from the advantages of unique nest-like nanoarchitecture and pseudocapacitive effect, the NiO hollow microspheres show high reversible capacity, superior cyclic performance, and excellent high rate capability. When used as anode materials for lithium ion batteries, the NiO hollow microspheres maintain a capacity of 650 mA h g −1 after 100 cycles at a current density of 1 A g −1 . The capacity retention is 93%, which corresponds to a very small capacity decay of 0.07% per cycle. In particular, even at an ultra-high current density of 10 A g −1, the NiO electrode still delivers a stable discharge capacity of 457 mA h g −1 .